2016
DOI: 10.1007/s11250-016-1103-9
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive performance and survival of Holstein and Holstein × Simmental crossbred cows

Abstract: Crossbreed dairy breeds, such as Holstein × dairy type of Simmental, have been generally used to improve fertility, udder health, and longevity of dairy herds. The aim was to compare the reproductive performance and survival of Holstein and Holstein × Simmental crossbred cows. Data from two farms were used as follows: one located in Bom Retiro, in the state of Santa Catarina, Brazil. and another in Carambeí, Paraná state. Information concerning birth, inseminations, and parity date were obtained from the manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 20 publications
2
21
3
Order By: Relevance
“…Moreover, Knob et al . (2016) highlighted better reproductive performance and higher survival rate in Holstein × Simmental crossbred cows than in Holstein cows.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, Knob et al . (2016) highlighted better reproductive performance and higher survival rate in Holstein × Simmental crossbred cows than in Holstein cows.…”
Section: Discussionmentioning
confidence: 99%
“…Crossbreeding between Simmental (dairy type) and Holstein has been performed for a long time, mostly in Europe. Several studies have demonstrated that relative crossbreds had higher reproductive performance and a better ability to restore immune homeostasis afther calving than Holstein cows (Knob et al ., 2016, 2020; Puppel et al ., 2018; Scatà et al ., 2020). Knob et al .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the crossbreed between Simmental and Holstein cows has been found to improve CR [34]. Equally, Knob et al [39] informed that crossbred Simmental × Holstein cows had good reproductive efficacy compared with Holstein cows, characterized by higher CR (37.3 vs. 33.6 %). It has been well documented that there is a close relationship among BCS, NEB, and fertility [8].…”
Section: Discussionmentioning
confidence: 99%
“…The crossing of Holstein and Simmental breeds aims to utilize the positive characteristics of each breed. Previous study showed improved fertility traits (shorter calving and calving to first service intervals) and prolonged longevity in HO × SI crossbred F1 population with respect to HO purebred (Knob et al ., 2016).…”
mentioning
confidence: 99%